Dakwah Dalam Persepektif Hasan Al-Banna - Noor Chozin Sufi (Al-Jami'ah: Journal of Islamic Studies, 2000)
Any movement requiring the involvement of people certainly needs careful plan and strategy in order to achieve its main goals, including "dakwah". In this article the writer tries to elaborate the concept and strategy of "dakwah" offered by an outstanding Muslim leader of Egypt, Hassan al-Banna. He is chosen since his thought has been influencing and inspiring Muslims all over the world. After giving considerable biographical notes of al-Banna the writer explains that according to al-Banna Islamic dakwah must cover and serve every aspect and basic need of human life, in other words it must be comprehensive. For this reason, to implement his thought on dakwah e built up a religions organization called Ikhwanul Muslimin which was managed professionally and provided services for people of Egypt.  This distinguished dakwah organization had colored the lives of the Egyptians for many decades and elevated their understanding on Islamic teachings. The phenomena of its success is still under discussion and inspiring many dakwah organizations in Indonesia.